MODELLING THE BEHAVIOUR OF HOUSEHOLD’S INVESTMENT - Widayat, Widayat; Wahjoedi, Wahjoedi; Idrus, M. Syafiâ€™ie (Economic Journal of Emerging Markets, 2011)
Household investment has become more important in modern economies. This research builds a behavioural model of investment using a quantitative approach. It tests the effect of socioeconomic condition, financial literacy, and attitudes toward intention and investment decision. The data are collected from 400 heads of household through a structured interview. A sample is selected by a multistage technique. It applies a Structural Equation Modelling to answer the research problem. This paper is successful in constructing a good structural and measurement model to explain the behaviour of the dependent variables in the model. Keyword: Behavioural model of investment, investment, quantitative, household JEL classification numbers: D1, D14